HUBUNGAN KADAR LIPID DARAH DENGAN DERAJAT KEPARAHAN NEUROPATI DIABETIK PERIFER DI RUMAH SAKIT WAHIDIN SUDIROHUSODO - Devina Irawan; Audry Devisanty Wuysang; Yudy Goysal (NEURONA, 2019)
CORRELATION BETWEEN BLOOD LIPID LEVELS AND SEVERITY OF DIABETIC PERIPHERAL NEUROPATHY IN WAHIDIN SUDIROHUSODO HOSPITALABSTRACTIntroduction: Blood lipid levels play a role in the etiopathogenesis of diabetic neuropathy and have a significant relationship to the severity of diabetic neuropathy in patients with diabetes mellitus (DM).Aim: To assess the correlation between blood lipid levels and the severity of diabetic peripheral neuropathy (DPN) based on nerve conduction study (NCS).Methods: A cross-sectional study at Wahidin Sudirohusodo General Hospital, Makassar, consecutively from December 2018 to March 2019 on type 2 DM patients with DPN based on screening for diabetic neuropathy symptoms. HbA1C and blood lipid levels were examined, and DPN severity based on NCS was assessed using electromyoneurography (ENMG) with England criteria. One-way ANOVA was used for correlation analysis.Results: There were 56 subjects with an average age of 60.25 years old, the majority was women (51.8%) with DM duration ≥5 years (62.5%), HbA1C levels of patients ≥7% (55.4%), dyslipidemia (76.8%), and experienced severe DPN (55.4%). There was a significant relationship between blood lipid levels and the severity of DPN (p<0.05), especially in subjects with a patient’s HbA1C level <7%.Discussion: High lipid level plays a role in etiopathogenesis of diabetic neuropathy.Keywords: Blood lipid levels, diabetic peripheral neuropathy, HbA1CABSTRAKPendahuluan: Kadar lipid darah berperan dalam etiopatogenesis neuropati diabetik dan memiliki hubungan signifikan terhadap derajat keparahan neuropati diabetik pada pasien diabetes melitus (DM).Tujuan: Menilai hubungan kadar lipid darah dengan derajat keparahan neuropati diabetik perifer (NDP) berdasarkan Nerve Conduction Study (NCS).Metode:  Penelitian  potong  lintang  di  RSUP  Wahidin  Sudirohusodo,  Makassar,  secara  konsekutif  periode Desember 2018-Maret 2019 terhadap pasien DM tipe 2 yang mengalami NDP berdasarkan skrining diabetic neuropathy symptoms. Dilakukan pemeriksaan kadar HbA1C dan lipid darah, serta penilaian derajat keparahan NDP berdasarkan KHS menggunakan alat elektromioneurografi (ENMG) dengan kriteria England. Analisis hubungan menggunakan uji one-way ANOVA.Hasil: Didapatkan 56 subjek dengan rerata usia 60,25 tahun, mayoritas perempuan (51,8%) dengan durasi DM ≥5 tahun (62,5%), kadar HbA1C pasien ≥7% (55,4%), dalam keadaan dislipidemia (76,8%), dan mengalami NDP berat (55,4%). Terdapat hubungan bermakna antara kadar lipid darah dan derajat keparahan NDP (p<0,05), terutama pada subjek dengan kadar HbA1C pasien <7%.Diskusi: Tingginya kadar lipid darah akan memperberat derajat keparahan NDP.Kata kunci: HbA1C, kadar lipid darah, neuropati diabetik perifer